The Russian Flat Tax Reform - Keen, Michael (IMF Working Papers; Working Paper, 2005)
Russia dramatically reduced its higher rates of personal income tax (PIT) in 2001 establishing a single marginal rate at the low level of 13 percent. In the following year, real revenue from the PIT actually increased by about 26 percent. This 'flat tax' experience has attracted much attention (and emulation) among policymakers, making it perhaps the most important tax reform of recent years. But it has been little studied. This paper asks whether the strong revenue performance of the PIT was itself a consequence of this reform, using both macro evidence and, in particular, micro-level data on the experiences of individuals and households affected by the reform to varying degrees. It concludes that there is no evidence of a strong supply side effect of the reform. Compliance, however, did improve quite substantially-by about one third according to our estimates-though it remains unclear whether this was due to the parametric reforms or to accompanying changes in enforcement.